Proceedings of 36th Biennial Meeting 2011
DOI: 10.5274/assbt.2011.82
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory losses in sugar beets as a function of storage temperature, field nitrogen application, sprouting incidence and handling severity

Abstract: Respiratory losses in sugar beets as a function of storage temperature, field nitrogen application, sprouting incidence and handling severity. The trend toward warmer temperatures in Michigan has lead to an increased risk of excessive temperatures in field piles of sugarbeets. In the 2004-2005 season, the Michigan industry is estimated to have lost approximately $25,000,000 to pile breakdown following an unusually warm winter and spring. Determination of optimal storage strategies requires knowing the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Sucrose content decreased by approximately 3–4% in the 60 days after harvest under the favorable storage conditions used in this study. The quantity of sucrose lost in this study was similar to that reported by Beaudry et al (2011) who observed a 3–9% decline in sucrose content for roots stored for 100 days under ideal conditions. Although a decline in sucrose of this magnitude may not be important for many crop or horticultural products, such a loss is economically important for a crop that is grown solely for the sucrose contained within.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Sucrose content decreased by approximately 3–4% in the 60 days after harvest under the favorable storage conditions used in this study. The quantity of sucrose lost in this study was similar to that reported by Beaudry et al (2011) who observed a 3–9% decline in sucrose content for roots stored for 100 days under ideal conditions. Although a decline in sucrose of this magnitude may not be important for many crop or horticultural products, such a loss is economically important for a crop that is grown solely for the sucrose contained within.…”
Section: Discussionsupporting
confidence: 90%
“…During this time, root sucrose content declines. Under ideal storage conditions, sugarbeet roots stored for 100 days lost 3–9% of the sugar present at harvest ( Beaudry et al, 2011 ). In commercial practice, ideal storage conditions are seldom achieved, and losses of 50% or more of the sucrose present at harvest have occurred in roots stored under unfavorable environmental conditions ( Kenter and Hoffmann, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sugarbeet root sucrose content and processing quality decline during storage, reducing the quantity of sugar that can be recovered during processing and increasing production costs. Losses of 3 to 10% of the sucrose present at harvest are reported for roots stored up to 100 d under favorable temperature conditions, but these can escalate to 50% or more if optimal pile temperatures are not obtained or maintained ( Kenter and Hoffmann, 2009 ; Beaudry et al., 2011 ; English, 2020 ). Processing quality deteriorates due to the formation and accumulation of carbohydrate impurities, such as glucose, fructose and raffinose, and cell wall modifications, that combined with root dehydration, soften roots ( Vukov and Hangyál, 1985 ; Dutton and Huijbregts, 2006 ).…”
Section: Introductionmentioning
confidence: 99%